RETRACTED: Assessment of sustainable behavior of environmental specialists - Dovlatova Galina; Tkacheva Olga; Smakhtina Anna; Bondarenko Olga; Zhukova Irina; Agafonov Anton (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001